Phosphorus fractions in soil after sucessive pig slurry applications in no-tillage system - Ceretta, Carlos Alberto; Lorensini, Felipe; Brunetto, Gustavo; Girotto, Eduardo; Gatiboni, Luciano Colpo; Lourenzi, Cledimar Rogério; Tiecher, Tadeu Luis; De Conti, Lessandro; Trentin, Gustavo; Miotto, Alcione (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to quantify the accumulation of phosphorus fractions in the soil subjected to successive pig slurry applications in a no-tillage system. At Santa Maria, Rio Grande do Sul state, Brazil, 0, 20, 40 and 80 m3 ha-1 doses of pig slurry were broadcasted for seven years on Argissolo Vermelho arenoso (Arenic Hapludult) before sowing each winter or summer crop, totalizing 0, 584, 1,168 and 2,336 kg ha-1 of P from pig slurry. Soil samples were collected in 0–2, 4–6, 8–10, 14–16 and 20–25 cm layers and submitted to P fractionation. Applications of pig slurry during seven years increased P contents to a depth of 25 cm, especially in the inorganic fractions extractable by anion exchange resin, NaHCO3 0.5 mol L-1 and NaOH 0.1 mol L-1. Pig slurry doses did not increase P content in organic fractions extracted by NaHCO3 0.5 mol L-1, but increased the content of organic fractions extracted by NaOH 0.5 e 0.1 mol L-1. Pig slurry applied to soil for large period has little effect on the P partition in inorganic and organic fractions. Successive pig slurry applications increase P contents in the soil predominantly in labile fractions, which can represent a potential risk for waterbeds contamination.